The Releation Between Vitamin D and Quality of Life - Pınar Akpınar; Afitap İçağasıoğlu (Galenos Yayinevi, 2015)
Aim: To explore the relation between vitamin D and quality of life. Material and Methods: 110 women aged 35 to 65 years were recruited in the study.The demographic data were recorded, and Short Form- 36 (SF-36) and Quality-of-Life Questionnaire of The European Foundation for Osteoporosis (QUALEFFO-41) scales were filled out. Patients were divided into three groups; 25(OH)D level <20 ng/ml regarded as vitamin D deficiency, 20-29 ng/ml as vitamin D insufficiency, >30 ng/ml as normal. Bone mineral density was measured by dual x-ray absorptiometry. Modified Romberg test for balance, Timed Get Up and Go test for mobility and 10 meter walk test for gait assesment were used. Results: There was a statistically significant relation-ship between body mass index, wearing style, physical activity and 25(OH)D levels (p<0.01). Also, there was a statistically significant correlation between L2-L4 z-scores and 25(OH)D levels (p<0.05). Although there was a statistically significant correlation between Modified Romberg test and 25(OH)D levels (p<0.05), there was no correletion with Timed Get Up and Go test and 10 meter Walk Test (p>0.05). There was a statistically significant correlation between 25(OH)D levels and SF-36 Physical Function, Vitality scores, QUALEFFO-41 Social Function and Total scores (p<0.05). Conclusion: Deficient or insufficient vitamin D levels impair quality of life. (Turkish Journal of Osteoporosis 2012;18:13-8)